Case report: Successful treatment of a patient presenting with a very rare association of acute lymphoblastic leukemia and mucopolysaccharidosis type IVA - Arnaboldi, Sofia Maria Carlotta; Faraguna, Martha Caterina; Colombini, Antonella; Sala, Alessandra; Leoni, Veronica; Spinelli, Marco; Gotti, Giacomo; Bettini, Laura Rachele; Crescitelli, Viola; Commone, Anna; Gasperini, Serena; Rizzari, Carmelo (Frontiers in Pediatrics, 2025)
Treating Acute Lymphoblastic Leukemia (ALL) in patients with genetic disorders poses significant challenges for onco-hematologists. Mucopolysaccharidosis type IVA (MPS-IVA) is a lysosomal storage disorder that clinically manifests with progressive and multi-systemic comorbidities, primarily affecting the bone, cartilage, spine, heart and lungs. We report a unique case of B-lineage ALL in a patient with MPS-IVA, who was successfully cured with a personalized chemo-radiotherapy approach. The treatment strategy aimed to balance a curative-intent chemotherapy attempt with the minimization of life-threatening complications. This case highlights the importance of individualized therapy in managing ALL in the context of complex comorbidities.